(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In order to stress the natural contro! agains citrus Leaf Miner (CLM) Phyllocnistis citrella Stainton in Sicily, during 1999 Citrostichus phyllocnistoides (Narayanan) has ben introduced and released in the field. It was bred together with Semielacher petiolatus (Girault) under seminatura! conditions. During the rearing it was observed that no competion between the two parasitoids occurred and that both species survived and multiplied although the temperature lasted above 40°C for many hours and in severa! days. The results emerged from the releases of C. phyllocnistoides in some CLM’ infested citrus groves look not only at its recoveries, but also at its probable establishment in Sicily.